2005
DOI: 10.1073/pnas.0503955102
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical metabolomics demonstrates substantial compositional similarity between genetically modified and conventional potato crops

Abstract: There is current debate whether genetically modified (GM) plants might contain unexpected, potentially undesirable changes in overall metabolite composition. However, appropriate analytical technology and acceptable metrics of compositional similarity require development. We describe a comprehensive comparison of total metabolites in field-grown GM and conventional potato tubers using a hierarchical approach initiating with rapid metabolome "fingerprinting" to guide more detailed profiling of metabolites where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
289
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(309 citation statements)
references
References 26 publications
13
289
0
3
Order By: Relevance
“…26 Metabolite changes that are observed in diseased individuals as a primary indicator have been an important part of clinical practice. 27 Metabolomics is the comprehensive assessment of endogenous metabolites and attempts to systematically identify and quantify metabolites from a biological sample.…”
Section: Bringing Metabolomics Into the Forefront Of Hcc Researchmentioning
confidence: 99%
“…26 Metabolite changes that are observed in diseased individuals as a primary indicator have been an important part of clinical practice. 27 Metabolomics is the comprehensive assessment of endogenous metabolites and attempts to systematically identify and quantify metabolites from a biological sample.…”
Section: Bringing Metabolomics Into the Forefront Of Hcc Researchmentioning
confidence: 99%
“…Compounds can be identified which determine the taste of some foods. Metabolomics has shown that genetically modified potatoes and tomatoes differ from normal ones by just a few compounds like fructans and flavonoids respectively [37,38]. Also, verification of labelled ingredients which we believe to be true can be achieved by metabolomics.…”
Section: Metabolomics In Food Industrymentioning
confidence: 88%
“…chromatography combined with mass spectrometry (MS) or nuclear magnetic resonance (NMR) spectroscopy is capable of detecting all metabolites within a given biological sample Hall, 2006;Allwood et al, 2008). Over the past decade many methods for the high-throughput metabolomic analysis of plant derived samples have been established for gas chromatography combined with MS (GC-MS; Fiehn et al, 2000;Fernie et al, 2004;Lisec et al, 2006), direct injection mass spectrometry (DIMS; Goodacre et al, 2003;Catchpole et al, 2005;Allwood et al, 2006), liquid chromatography MS (LC-MS; Tolstikov et al, 2003;Jander et al, 2004;von Roepenack-Lahaye et al, 2004;Vorst et al, 2005;Moco et al, 2006;Rischer et al, 2006;De Vos et al, 2007), capillary electrophoresis MS (CE-MS; Sato et al, 2004), and 1 H-NMR (Ratcliff e and Shachar-Hill, 2001;Le Gall et al, 2003;Ward et al, 2003;Choi et al, 2004Choi et al, , 2006. 1 H-NMR has proven to be an appropriate tool for untargeted plant metabolomics, especially where studies focus upon samples that contain highly abundant bulk metabolite species, for example sugars in fruits (Biais et al, 2009).…”
mentioning
confidence: 99%
“…1 H-NMR has the advantage that it produces signals that correlate directly and linearly with compound abundance (Lewis et al, 2007), although for many studies it lacks the sensitivity required to obtain information on low-level metabolites that can alternatively be 34 provided by MS based approaches. DIMS provides a rapid (∼2 min per sample) metabolite fi ngerprint (Goodacre et al, 2003;Allwood et al, 2006), which has proven to be valuable for a fi rstround screen of material (indicating robust sample growth, collection and extraction methods) prior to more expensive and time-consuming chromatography combined with MS approaches (Catchpole et al, 2005). DIMS is also gaining in popularity with the advent of high-resolution and -precision Fourier transform ion cyclotron resonance (FT-ICR)-MS instruments (Aharoni et al, 2002;Hirai et al, 2004;Southam et al, 2007), although without the application of chromatography, DIMS alone cannot resolve isobaric metabolites.…”
mentioning
confidence: 99%
See 1 more Smart Citation